PENGENDALIAN KUALITAS DENGAN METODE SEVEN TOOLS DAN FMEA DI CV. BABYPRO JAKARTA - Yovita Yovita; Siti Rahayu; Veny Megawati (Perpustakaan Universitas Surabaya, 2018)
This research aims to know how to implement seven tools and FMEA method in CV. Babypro. Conducted observations inform that there are defects situated in the production cycle, that is the amount of defects resulted which are over the limit set by the firm, 3%. The result shows that the production cycle is still out of control and the highest defects generated by machine hemming. The corrective actions suggested to the firm are making the SOP that will discipline the workers, keeping the machine maintenanced periodically, revising the partnership contract with the supplier and the outsourcing firm, and developing clean habit to the workers.